Predictors of the Effectiveness of Psychological Support in Addition to the Base Treatment in Pulmonary Tuberculosis - V. M. Kolomiets; A. L. Kovalenko; E. P. Pavlenko; A. Yu. Petrov; E. V. Talikova (Антибиотики и Химиотерапия)
The aim of the study was to investigate the effect on the psycho-emotional state and adherence to treatment in patients with pulmonary tuberculosis of remaxol inclusion in the accompanying therapy regimens.Material and methods. The data from 326 patients (252 men and 74 women) with various forms of pulmonary tuberculosis treated at the Regional Clinical Tuberculosis Dispensary were analyzed; the average age of patients was 41.3±1.6 years. A low level of adherence to treatment, as well as clinical and laboratory signs of grade I hepatotoxicity were revealed in patients receiving a course of etiotropic therapy in the main group (N=72). In this regard, in addition to the psychological support for the main course of treatment, accompanying therapy was prescribed: remaxol 400 ml intravenous drip every other day (course No. 5), after-wards — 1 time a week (course No. 4). Patients in the comparison group (N=254) received standard treatment. In addition to the standard examination, the cytokine profile (the level of IL-1β, 4, 6), TNF-α and IFN-γ) was determined in dynamics according to the indications in patients. The level of adherence to the treatment was also determined in dynamics through testing according to the original methodology.Results. The study revealed that the inclusion of remaxol in the treatment regimens facilitated more pronounced positive dynamics in clinical and laboratory data compared with the standard regimen: a decrease in signs of hepatotoxicosis and a tendency towards improvement in cytokine profile parameters. This contributed to maintaining the etiotropic therapy regimen and improving the well-being of patients, which, in turn, increased the level of adherence and therefore the effectiveness of treatment in patients.Conclusions. The combination of positive effects of remaxol use in patients with pulmonary tuberculosis contributes to an increase in their psycho-emotional state and thereby increases adherence to treatment and its effectiveness.